The Patient’s Right to Self-Determination as a Foundational Human Right in Healthcare - Bagçeci, Hamide (The Age of Human Rights Journal, 2025)
The patient’s right to self-determination represents a break from medical paternalism in healthcare law. Although not always explicitly codified, this study argues that the right is constitutionally guaranteed through a holistic reading of dignity, autonomy, and bodily integrity. Framed as a hybrid constitutional right, it imposes both negative and positive obligations on the state. As a ‘precondition right’, it underpins all other healthcare entitlements. Although widely recognized in theory, restrictive practices—such as bans on abortion, euthanasia, and advance directives—show that this acceptance has not been consistently realized, underscoring the need to secure it as an implicit constitutional right.